Efficacy of COVID-19 vaccination in organized group: results of a prospective study - I. O. Stoma; E. S. Korsak; E. V. Voropaev; O. V. Osipkina; A. A. Kovalev; O. L. Tumash; D. D. Redko (Журнал инфектологии, 2023)
Objective: to assess the efficacy of COVID-19 vaccination against in organized group.   Materials and methods: A total of 122 adults, employees of a higher education institution participated in the study. Study participants were observed prospectively and filled out a questionnaire where they indicated their age, presence of chronic diseases, history of COVID-19 and vaccination status.   Findings: the study participants were divided into two groups: 59 vaccinated (48.36 %) and 63 unvaccinated (51.64 %) individuals with no differences in age between the groups. There were significantly fewer confirmed cases of COVID-19 in the vaccinated group (р = 0,0008457, df = 1; χ2 = 11,138), significant differences (p = 0.0084; df = 4; χ2 =13.678) were observed in the number of cases among study participants based on their vaccination status.   Conclusion: participants diagnosed with pneumonia were 75 % unvaccinated (p = 0,00729; df = 1; χ2 = 7,2). All hospitalized study participants were unvaccinated (p = 0,004678; χ2 =8,0). None of the vaccinated participants needed respiratory support (p = 0,0455; df = 1; χ2 = 4,0). Chronic disease in vaccinated subjects made a significant (p = 0,04563; df = 2; χ2 = 6,1743) impact on COVID-19 severity.